2016
DOI: 10.1177/1461444816634054
|View full text |Cite
|
Sign up to set email alerts
|

Political rumoring on Twitter during the 2012 US presidential election: Rumor diffusion and correction

Abstract: Social media can be a double-edged sword for political misinformation, either a conduit propagating false rumors through a large population or an effective tool to challenge misinformation. To understand this phenomenon, we tracked a comprehensive collection of political rumors on Twitter during the 2012 US presidential election campaign, analyzing a large set of rumor tweets (n = 330,538). We found that Twitter helped rumor spreaders circulate false information within homophilous follower networks, but seldom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(93 citation statements)
references
References 49 publications
3
82
2
6
Order By: Relevance
“…These results contribute to the existing literature on attacks against public figures and journalists (Barlow and Awan, 2016;Johnen et al, 2018;Preuss et al, 2017;Shin et al, 2017), which is largely anecdotal and limited to women. Our results enrich this literature by a theoretically driven and quantitative comparison of the prevalence rate of three avoidance strategies for both genders and two contrasting explanations of gendered avoidance.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These results contribute to the existing literature on attacks against public figures and journalists (Barlow and Awan, 2016;Johnen et al, 2018;Preuss et al, 2017;Shin et al, 2017), which is largely anecdotal and limited to women. Our results enrich this literature by a theoretically driven and quantitative comparison of the prevalence rate of three avoidance strategies for both genders and two contrasting explanations of gendered avoidance.…”
Section: Discussionsupporting
confidence: 65%
“…Generally, public figures such as politicians, celebrities, popular academics, and journalists have become highly exposed and accessible. This has made them easy targets for shaming, defamation, and trolling (Barlow and Awan, 2016;Johnen et al, 2018;Preuss et al, 2017;Shin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This is also confirmed by [62], who concluded that rumor spreaders form strong partisan structures. Del Vicario also shows that different types of misinformation propagate differently.…”
Section: Misinformation Dynamicssupporting
confidence: 75%
“…It has also been suggested that corrections are usually issued by news organisations and they can be sometimes widely spread (Takayasu et al 2015;Arif et al 2016;Andrews et al 2016), especially if those corrections come from like-minded accounts (Hannak et al 2014) and occasionally even leading to deletion or unsharing of the original post (Frias-Martinez et al 2012). However, corrections do not always have the same effect as the original rumours (Lewandowsky et al 2012;Shin et al 2016;Starbird et al 2014), which reinforces the need to develop rumour classification systems that deal with newly emerging rumours.…”
Section: Characterising Rumours: Understanding Rumour Diffusion and Fmentioning
confidence: 99%